2018
DOI: 10.1152/ajpendo.00285.2017
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and other dietary polyphenols: potential mechanisms of metabolic actions and therapy for diabetes and obesity

Abstract: Recent controversy regarding the therapeutic potential of curcumin indicates the challenges to research in this field. Here, we highlight the investigations of curcumin and other plant-derived polyphenols that demonstrate their application to metabolic diseases, in particular, obesity and diabetes. Thus, a number of preclinical and clinical investigations have shown the beneficial effect of curcumin (and other dietary polyphenols) in attenuating body weight gain, improving insulin sensitivity, and preventing d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 60 publications
2
84
0
1
Order By: Relevance
“…This, along with other chemistry features of curcumin, has generated enormous difficulties in the detailed dissection of mechanistic pathways underlying its bio-medical functions. Indeed, these features have been causing some confusion among drug developers and have been heavily debated recently [82][83][84][85] . However, investigations presented by numerous investigators, including our team, suggest that the implications of dietary polyphenol research are beyond the scope of drug development.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…This, along with other chemistry features of curcumin, has generated enormous difficulties in the detailed dissection of mechanistic pathways underlying its bio-medical functions. Indeed, these features have been causing some confusion among drug developers and have been heavily debated recently [82][83][84][85] . However, investigations presented by numerous investigators, including our team, suggest that the implications of dietary polyphenol research are beyond the scope of drug development.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…In animal models of experimental CKD, curcumin protects against mitochondrial dysfunction and decreases oxygen consumption by reducing ROS production . However, it has been reported that curcumin is somewhat difficult to study since it is rapidly degraded in vivo and have very low bioavailability . Curcumin, as well as other polyphenols, activates Nrfā€2 and stimulates an antioxidant response .…”
Section: Nutritional Strategies Targeting Mitochondrial Dysfunction Imentioning
confidence: 99%
“…63,64 However, it has been reported that curcumin is somewhat difficult to study since it is rapidly degraded in vivo and have very low bioavailability. 65 Curcumin, as well as other polyphenols, activates Nrf-2 and stimulates an antioxidant response. 66 Even though knowledge of the exact molecular activity of this polyphenol is limited, it has been thoroughly studied in relation to cancer.…”
Section: Targeting Mitochondrial Dysfunction In Ckdmentioning
confidence: 99%
“…Chronic systemic inflammation has been proposed as the main factor in the development and progression of several noncommunicable diseases, including metabolic syndrome, cardiovascular diseases, obesity, and cancer (Namazi, Larijani, & Azadbakht, ). Several mechanisms have been proposed for effects of antiā€inflammatory diets and their ingredients such as curcumin on obesity and WC including inhibition of the lipogenesis and inflammation (reducing proinflammatory cytokines), suppressing angiogenesis in adipose tissue, downregulating preadipocyte differentiation, increasing lipolysis, brown fat tissue, adipocyte energy metabolism and apoptosis, serum levels of nesfatin, and probioticsā€like effects (Jin, Song, Weng, & Fantus, ; Navekar et al, ; Zhang, Fu, Gao, & Liu, ). The effects of nesfatin include appetite loss, reducing body fat, antiā€inflammation, antihyperglycemic, metabolic, and neuroendocrine regulation (Dong et al, ; Shen, Han, Cai, & Wang, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic systemic inflammation has been proposed as the main factor in the development and progression of several noncommunicable diseases, including metabolic syndrome, cardiovascular diseases, obesity, and cancer (Namazi, Larijani, & Azadbakht, 2018). (Jin, Song, Weng, & Fantus, 2018;Navekar et al, 2017;Zhang, Fu, Gao, & Liu, 2013). The effects of nesfatin include appetite loss, reducing body fat, anti-inflammation, antihyperglycemic, metabolic, and neuroendocrine regulation (Dong et al, 2013;Shen, Han, Cai, & Wang, 2015).…”
Section: Publication Biasmentioning
confidence: 99%